Waxing lyrical: ancient medical authors on wax and wax tablets - Totelin, Laurence (DELTOS, 2024)
This short survey discusses some of the uses of wax in ancient medicine: it was a key pharmacological ingredient; it served to create models of surgical tools; and it was a support for the writing of ancient recipes. Physicians distinguished between different types of wax, some of which were considered more efficacious than others. Wax could be consumed orally, but most commonly entered in the production of salves (cerates).